Developing, Administering, and Scoring the Healthcare Ethics Consultant Certification Examination - Bruce, Courtenay R. (The Hastings Center report, 2019)
In November 2018, the practice of health care ethics consultation crossed a major threshold when 138 candidates took the inaugural Healthcare Ethics Consultant Certification Examination. This accomplishment, long in the making, has had and continues to have both advocates and critics. The Healthcare Ethics Consultant Certification Commission, a functionally autonomous body created and funded by the American Society for Bioethics and Humanities, was charged with overseeing creation of the certification process, developing the exam, and formulating certification standards and policies to assess candidates’ qualifications. In this essay, as members of the commission, we describe the process of developing, administering, and scoring the certification examination as well as the historical context and the outlook for certification. By detailing the decisions and actions of the commission, we aim to provide a transparent account of the commission's efforts to develop a psychometrically sound, reliable, and secure examination through a deliberative, fair, and data-driven process.